A squaraine-based colorimetric probe for the sensitive detection of copper ion (II). Issue 1 (1st November 2022) - Du, Bin; Mu, Xihui; Liu, Zhiwei; Geng, Shu; Wang, Jiang; Xu, Jianjie; Chen, Lina; Tong, Zhaoyang
Abstract : A squaraine based colorimetric probe 2, 4-bis[4-( N, N -diisobutylamino)-2, 6-dihydroxyphenyl]squaraine (IHSQ) was selected for colorimetric detection of Cu 2+ and the characteristics of IHSQ for Cu 2+ recognition were investigated by absorption spectra. The results showed the absorbance of IHSQ significantly decreased with increasing concentration of Cu 2+ in acetonitrile/H2 O ( V/V = 9/1). This colorimetric detection method shows a satisfactory linear response (R 2 = 0.9856) to Cu 2+ concentration within the range from 2 μM to 200 μM. The limit of detection was 2 μM which was much lower than the environmental protection agency guideline of China (15.63 μM) in drinking water. Moreover, no obvious interference was observed on the detection of the Cu 2+ in the presence of the common metal ions such as Zn 2+, K +, Ca 2+, Na +, Co 2+, Ba 2+, Cd 2+, Cr 3+, Sr 2+, Pb 2+ and Fe 3+, indicating that IHSQ possesses high selectivity and satisfactory sensitivity for the detection of Cu 2+ .